The Development Of Science Literacy Based Digital Teaching Materials To Improve Students Critical Thinking On The Sub Matter Of Energy Flow And Biogeochemical Cycles - Fayca Febi Tiara; Ibnul Mubarok (Universitas Negeri Semarang, 2023)
This study aims to develop science literacy-based digital teaching materials that are feasible, practical, and effective for improving students' critical thinking on the sub-materials of energy flow and biogeochemical cycles. This type of research is research and development (RnD). The method used in research and development refers to the ADDIE development model. The population in this study were students in grades XI Mipa and X SMA Negeri 15 Semarang in the 2022/2023 academic year. MIPA 7 for small-scale trials and 60 students from each of 30 students X-1 and X-2. The data collection techniques used were interviews, questionnaires and tests. Based on data analysis, the feasibility test results of science literacy-based digital teaching materials by material experts amounted to 85% and media experts amounted to 82%. The results of the practicality test analysis by teachers in both scale trials were 90% and the results of the practicality test analysis by students in both scale trials were 84%. From all the results of the analysis, it is included in the category of very feasible and practical. To determine the effectiveness of science literacy-based digital teaching materials, pretests and posttests in classes X-1 and X-2 were conducted and then calculated using the N-Gain test based on aspects. The results of the N-Gain test for the science literacy aspect in both classes were 0.64% and the N-Gain test for the critical thinking ability aspect in both classes was 0.62%. This shows that classes X-1 and X-2 on improving science literacy and critical thinking skills are at moderate criteria. It can be concluded that the use of science literacy-based digital teaching materials is effective for improving students critical thinking skills in the sub-materials of energy flow and biogeochemical cycles.